Relationship of Perceived Ease of Use, Trust, Customer Satisfaction and Customer Loyalty in E-Commerce: A Case Study of The Shopee Application - Anwar, Muhamad Syaeful; Verawati, Liesta; Afiati, Lely (Fakultas Pendidikan Ekonomi dan Bisnis, 2024)
Purpose – The purpose of the study is to provide empirical evidence on the impact of perceived ease of use and trust on customer satisfaction and, in turn, how customer satisfaction influences customer loyalty in the context of the Shopee application.Design/methods/approach – The study employs a quantitative research approach. Data was collected through surveys distributed to Shopee users. The analysis used Structural Equation Modeling (SEM) to test the hypothesized relationships between perceived ease of use, trust, customer satisfaction, and customer loyalty.Findings – The findings indicate that perceived ease of use and trust positively and significantly affect customer satisfaction. Additionally, customer satisfaction has a positive and significant impact on customer loyalty. This suggests that improving the ease of use and trustworthiness of the Shopee platform can enhance customer satisfaction, leading to greater customer loyalty.Research implications/limitations – Implications: The results provide practical insights for e-commerce platforms, particularly Shopee, highlighting the importance of emphasizing ease of use and building trust to improve customer satisfaction and loyalty. Limitations: The study's limitations include its focus on a single ecommerce platform (Shopee), which may not generalize to other platforms. Future research should consider including multiple ecommerce platforms to expand the findings. Additionally, only customer loyalty was used as a dependent variable; future studies could explore other dependent variables related to customer behavior.Originality/value – This research adds value by offering new insights into customer satisfaction and loyalty dynamics in the e-commerce sector, specifically within the Shopee platform. It underscores the critical roles of perceived ease of use and trust in fostering customer satisfaction and loyalty, which can guide e-commerce businesses in strategic planning and customer relationship management